Respuesta :

Answer:

B. Multiply the binomial by 3.  

Step-by-step explanation:

We have been given an expression: [tex]11x-2-3(1-7x)^2\div(x+1)[/tex]. We are asked to determine the first step in simplifying the expression.

Since we know that the order of operations is also known as PEMDAS, where,  

P= Parenthesis,

E= Exponents,

M= Multiplication,  

D = Division,

A =Addition,

S = Subtraction.

According the order of operations we will distribute 3 to binomial or multiply the binomial by 3. Therefore, option B is the correct choice.


Answer:

Its A

Step-by-step explanation:

good luck i just finished it